Young people’s perception of the measures taken by the authorities in the context of the Covid-19 pandemic - Mari-Isabella Stan; Rus, Mihaela; Tasente, Tanase (Technium Social Sciences Journal, 2020)
Transparency is generally defined by political scientists as the principle of allowing the public to obtain information about the operations and structures of a given entity (Etzioni, 2014). Transparency symbolizes a mechanism for promoting good governance and public confidence in a modern and democratic public administration (Jashari and Pepaj, 2018). The theory of open public administration gives the individual a greater role in the adoption of the executive regulations and greater transparency in the operations of the public administration (Bugaric, 2004). A fully transparent administration, either at central level or at local level, involves informing and participating citizens in the decision-making process, becoming an indispensable principle of the rule of law. On the other hand, democratic citizenship involves obtaining information about the problems that affect you and working with others to influence how society will solve those problems (Portelli and Solomon, 2001). The objectives of the study are: (1) Identification of the degree of knowledge of the concept of decision-making transparency in public administration; (2) Analysis of the perception regarding the degree of decision-making transparency and communication of the local and central public administrations in the context of the crisis generated by the Covid-19 pandemic; (3) Analysis of the degree of confidence the crisis management generated by the new Coronavirus by public institutions. The questionnaire, which included 10 items, was applied, on a sample consisting of 200 students and graduates of the Faculty of Law and Administrative Sciences - “Ovidius” University of Constan?a (Romania, European Union). The period of application of the questionnaire was April 4-10, 2020. Of these, 80.77% are female, and 19.23% are male, with an average age of 27.5 years. Most of the respondents (56.41%) are undergraduate students, and the remaining 43.59% are study participants are graduates or masters of the same Faculty. At the same time, 71.79% of the study participants come from urban areas, and 28.21% from rural areas.